Pengaruh Dosis Mol Campuran Daun Kelor dengan Leri Terhadap Pertumbuhan dan Hasil Tanaman Pakcoy (Brassica rapa L.) Varietas Gardena - sagustian futuhi ahlaa; Sunawan Sunawan; Agus Sugianto (AGRONISMA, 2022)
Pakcoy (Brassica rapa L.) is one of the most widely cultivated and consumed horticultural crops in Indonesia. The aim of this research is to increase the yield of mustard pakcoy by giving various doses of MOL mixed with Moringa and Leri leaves so that it is expected to increase the productivity of mustard pakcoy. The design used was a simple RAK experimental design where there were 5 levels, namely K0 = without MOL application, K1 = 200 ml/plant, K2 = 250 ml/plant, K3 = 300 ml/plant, and K4 = 350 ml/plant. The results showed that the MOL mixture of Moringa and Leri leaves for K1 treatment with a dose of 200 ml/plant gave the best effect on plant height of 25.50 cm, number of leaves of 9.58 strands, leaf area of 1154.65 cm2, and total fresh weight of 315.25 g.. The optimal dose of MOL mixture of moringa leaves with leri is 153.14 ml/plant with the total fresh weight of the plant was 302.83 g.Â Keywords : pakcoy, MOL mixture of moringa leaves with leri, , yield of pakcoy